Bacterial cell motility ofBurkholderia gut symbiont is required to colonize the insect gut. Issue 19 (28th August 2015) - Lee, Jun Beom; Byeon, Jin Hee; Jang, Ho Am; Kim, Jiyeun Kate; Yoo, Jin Wook; Kikuchi, Yoshitomo; Lee, Bok Luel
Abstract : We generated a Burkholderia mutant, which is deficient of an N ‐acetylmuramyl‐l ‐alanine amidase, AmiC, involved in peptidoglycan degradation. When non‐motile Δ amiC mutant Burkholderia cells harboring chain form were orally administered to Riptortus insects, Δ amiC mutant cells were unable to establish symbiotic association. But, Δ amiC mutant complemented with amiC gene restored in vivo symbiotic association. Δ amiC mutant cultured in minimal medium restored their motility with single‐celled morphology. When Δ amiC mutant cells harboring single‐celled morphology were administered to the host insect, this mutant established normal symbiotic association, suggesting that bacterial motility is essential for the successful symbiosis between host insect and Burkholderia symbiont. Abstract : Burkholderia Δ amiC mutant showed defect in cell separation and decreased motility. Non‐motile Δ amiC mutant cells were unable to symbiotically associate with host insect. Δ amiC cells cultured in minimal media restored their motility. Motile Δ amiC cells successfully established association with host. Cell motility of Burkholderia symbiont is important for symbiosis with host insect.